The Medellin Consumer: LOCAL OR GLOBAL? A PSYCHOGRAPHIC APPROACH (2019)
The present process of globalization have led to relevant changes in the supply and demand of all economies and in the standardization tendencies of business. In view of this, a question arises: What happens with the regional conglomerates of consumption? Such a question brought us to the consolidation of a study on the profile of the consumer in Antioquia (please see geographical location on paragraph 2 below); the results shown here include five great conglomerates (or clusters) obtained by multivariate analysis, from the population of strata three, four and five of the city of Medellín. This constitutes the accomplishment of a first step in the line of studies on the behavior of the Antioquian Consumer. The central idea has been to investigate the relevant aspects in matters of consumption of a representative cluster of the Medellín population. The purpose of this effort is to enhance the education processes on the subject, and to give account of the changes generated by the process of economic liberalization initiated ten years ago in Colombia.